2011
DOI: 10.1111/j.1556-4029.2010.01658.x
|View full text |Cite
|
Sign up to set email alerts
|

A Re‐examination of Cremains Weight: Sex and Age Variation in a Northern California Sample*

Abstract: The reduction of modern commercially cremated remains into a fine powder negates the use of traditional methods of skeletal analysis. The literature on the use of cremains weight for estimating aspects of the biologic profile is limited, often with conflicting results. This study re-evaluates the value of weight in the assessment of biologic parameters from modern cremated remains. A sample of adults was collected in northern California (n = 756), with a cremains weight averaging 2737.1 g. Males were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 18 publications
(44 reference statements)
2
33
0
Order By: Relevance
“…Several studies have demonstrated significant sex differences in cremains weight, with males weighing approximately 1000 g more than females . Van Deest et al.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated significant sex differences in cremains weight, with males weighing approximately 1000 g more than females . Van Deest et al.…”
Section: Resultsmentioning
confidence: 99%
“…Weights less than expected may point to remains that are either incomplete (i.e., some portion of the remains have been removed prior to examination) or those of a juvenile or nonhuman. All things considered, the weight of the cremated remains should correspond with published values for the sex and general skeletal robusticity of the decedent (Warren and Maples, 1997;Bass and Jantz, 2004;Van Deest et al, 2011).…”
Section: Cremation Weightsmentioning
confidence: 97%
“…Cremation research by physical anthropologists was initially geared towards identifying cremains based on recognisable bone and nonosseous artifacts (Murray and Rose, 1993;Huxley, 1994;Kennedy, 1996;Murad, 1998;Warren and Schultz, 2002), cremation weights (Warren and Maples, 1997;Bass and Jantz, 2004;Van Deest et al, 2011) and descriptions of the commercial cremation process (Eckert et al, 1988;Murad, 1998;Warren and Schultz, 2002). However, due to the efficiency of the newest processing methods, traditional gross methods of cremation analysis may be of limited value when trying to determine the identity and composition of purported cremains.…”
Section: Introductionmentioning
confidence: 99%
“…The expected range of the weight of cremated remains is well documented for various areas around the country (Bass and Jantz 2004;Sonek 1992;Van Deest et al 2011;Warren and Maples 1997). Cremains weight has been correlated to several aspects of the biological profile.…”
Section: The Biological Remainsmentioning
confidence: 97%
“…This problem is particularly vexing because it is common for cremated remains to be divided among family members. Although research into cremains weight indicates correlations with aspects of the biological profile, more research is needed to examine the full range of cremains weights from a number of different crematories due to the demonstrated differences in mean weights between different crematoria and different regions (Bass and Jantz 2004;Birkby 1991;Sonek 1992;Van Deest et al 2011;Warren and Maples 1997).…”
Section: The Biological Remainsmentioning
confidence: 98%